PERBANDINGAN WAKTU SADAR EFEKTIF (WSE) DALAM RUANG UDARA BERTEKANAN RENDAH (RUBR) KETINGGIAN SETARA 25.000 KAKI PADA SAAT MENJADI CALON PENERBANG DAN SETELAH MENJADI PENERBANG TNI AU DI LAKESPRA dr. SARYANTO - Salsabila Wardani, (2023)
Hypoxia is a state of decreased oxygen supply to tissues below the human physiological level. The incidence of hypoxia causes problems so pilot need training, namely Aerophysiology Training Indoctrination using a Hypobaric Chamber by looking for signs of hypoxia and the value of the Time of Useful Consciousness (TUC). Time of Useful Consciousness (TUC) is defined as the time a pilot can effectively perform a flight task in an oxygen depleted environment. Altitudes of 25,000 feet have an average TUC of 3 to 5 minutes. This research was conducted to find out the TUC comparasion in the Hypobaric Chamber with an altitude equivalent to 25,000 feet when becoming a plito candidate and after becoming a pilot. This research is an analytic observational study with a cross- sectional method. The study used a total sampling of 43 respondents, namely data for all prospective pilot and pilots at Lakespra dr.Saryanto met the inclusion criteria. The results show that there is a comparison of TUC when becoming a prospective pilot with TUC after becoming a pilot at an altitude equivalent to 25,000 feet (p = 0.035). The prospective pilot group found that 35 people (81.4%) had a TUC >3 minutes and 8 people (18.6%) had a TUC <3 minutes. In the pilot group, 28 people (65.1%) had a TUC >3 minutes and 15 people (34.9%) had a TUC <3 minutes.There is a comparison of TUC in Hypobaric Chamber equivalent to 25,000 feet at the time of becoming a pilot candidate and after becoming a pilot.